Probiotics : immunobiotics and immunogenics (Taylor & Francis, 2014)
"Written by international experts, this book reviews recent, cutting-edge research on the use of immunoregulatory probiotics (immunobiotics) and their bioactive compounds (immunogenics) to prevent and improve health. Each chapter provides critical insight, reviews current research, discusses future perspective, and stimulates discussion. The book also dicsusses novel applications of immunobiotics such as their use in respiratory infections, regulation of the interaction between inflammation and coagulation as well as their effect on hematopoiesis"--Provided by publisher.
Keywords: Probiotics.; Immune system.; elektronické knihy; electronic books